Writing and implementing a marketing plan - Gerson, Richard F. (Crisp Pub. Menlo ParkUS, 1991)
Explains the pre-planning process for a marketing plan which includes writing a mission statement and a seven-section business plan. Shows how to write a marketing plan and includes the following techniques for implementing it: advertising in the print media, on radio or on television; using brochures, contests, mailing lists, sales letters, business cards etc.